An Approach to Correlate Chemical Pretreatment to Digestibility Through Biomass Characterization by SEM, FTIR and XRD - Sunkar, Bindu; Bhukya, Bhima (Frontiers in Energy Research, 2022)
A comprehensive study was carried out to assess the efficiency of different chemicals on pretreatment of plant biomass, corn cobs. The efficiency was assessed based on its effect on subsequent hydrolysis of the biomass for the conversion to fermentable sugars. Both alkali and acid-based pretreatments were carried out under optimized conditions to avoid the formation of inhibitors and also to yield more sugars. Among the different chemicals used, 2% NaOH (w/v) was found to be effective with the delignification efficiency of 84.32% and further, the biomass saccharification efficiency was found to be 86.28% using 1.20% (v/v) HNO3 at 100 ºC for 90 min. Whereas the pretreatment with other chemicals including KOH, NaClO2, Na2SO3, NH3 had significantly (p<0.05) low delignification which ultimately reduced the saccharification efficiency. Whereas in acid-based pretreatment, 1.5% (v/v) HNO3 resulted in 63.42% delignification along with 68% digestion of hemicelluloses. The effect of pretreatment efficiency on digestibility was investigated by biomass characterization using SEM, FTIR and XRD analysis before and after the treatment process. The imaging studies clearly indicated that 2% NaOH efficiently digested the complex matrix alignment and enhanced the surface area of the carbohydrate polymer which had shown a positive impact on the rate of hydrolysis. The study concludes that the alkali-based pretreatment is the efficient and cost viable technique for the effective valorization of corn cobs for the production of fermentable sugars which can be further converted to various valued bioproducts.